1998
DOI: 10.1021/js970370u
|View full text |Cite
|
Sign up to set email alerts
|

Meropenem Exists in Equilibrium with a Carbon Dioxide Adduct in Bicarbonate Solution

Abstract: 0 Evidence is provided for the existence of a second discrete chemical form of meropenem at clinically relevant concentrations prepared from the marketed formulation of the drug. Proton and carbon-13 NMR spectra in D 2 O, coupled with tandem mass spectroscopy (MS/MS) and cross polarization/magic angle spinning (CP-MAS) NMR experiments, allow structural assignment of the compound as a covalent carbon dioxide adduct of meropenem. This carbon dioxide adduct exists in equilibrium with the free drug in solution and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…41,42 For carbapenems, mainly meropenem, some works have described the NMR analysis to characterize the antibiotic, the degradation products and impurities. [15][16][17]43 In the present work, the chemical structure of doripenem ( Figure 1) was confirmed based on the signals obtained in the spectra. The 1 H and 13 C NMR data were interpreted and the results are showed in Table 2.…”
Section: Nmrsupporting
confidence: 75%
See 1 more Smart Citation
“…41,42 For carbapenems, mainly meropenem, some works have described the NMR analysis to characterize the antibiotic, the degradation products and impurities. [15][16][17]43 In the present work, the chemical structure of doripenem ( Figure 1) was confirmed based on the signals obtained in the spectra. The 1 H and 13 C NMR data were interpreted and the results are showed in Table 2.…”
Section: Nmrsupporting
confidence: 75%
“…11,12 For other carbapenems, the works also focus on quantitation by LC, UV spectrophotometry and microbiological assay, applied on stability studies. [13][14][15] For meropenem, Almarsson et al 16 reports the analysis of the drug by proton and 13-carbon NMR coupled with tandem mass spectroscopy, which showed evidence that the structure is stable as CO 2 adduct, in solid state and in solution. Nishimura et al 17 describes the structural analysis of meropenem by 1 H NMR and X-ray diffraction, comparing to other penems and carbapenems.…”
Section: Introductionmentioning
confidence: 99%
“…It had been previously reported that the degradation of carbapenem antibiotics, imipenem and meropenem, followed a pseudo-first-order degradation in an aqueous solution, and the initial concentration was considered to affect the degradation of the drugs. [7][8][9][10][11] However, the mechanism of how the concentration affected the degradation had not been elucidated.…”
mentioning
confidence: 99%
“…6. (11) In Eq. 11, A is the frequency factor, E a is the activation energy, R is the gas constant (Rϭ1.987 cal mol Ϫ1 K…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7][8][9][10][11] As for its stereochemistry, panipenem exists as either the Z-form or E-form depending on the position of the acetimidoyl group. 12) A certain isomer type can be obtained depending on the solvent used in the recrystallization process; the E/Z mixture, E-form, and Z-form can be obtained, by using acetone, methanol, and ethanol as the recrystallization solvent, respectively.…”
mentioning
confidence: 99%